Teak (Tectona grandis) silviculture and research: applications for smallholders in Lao PDR. (15th May 2019) - Pachas, A. N. A.; Sakanphet, S.; Midgley, S.; Dieters, M.
ABSTRACT: Teak is an important forest plantation species in Lao PDR (Laos), that has been planted extensively by smallholders, supplying domestic industries and international markets. There have been significant advances in the intensive silvicultural management of teak focused on the production of high-quality timber. Laos is not an exception. With support from the Australian Centre for International Agricultural Research, there have been advances in the understanding and knowledge of appropriate management practices for smallholder teak, as well as development of supporting technologies (i.e. ex situ conservation, genetic improvement, growth models, thinning and pruning prescriptions, and agroforestry systems). This paper summarises published information on the silviculture and management of teak, including improvement of genetic resources, stocking rate, thinning and agroforestry systems used in Asia, Africa, Latin America and Oceania, and relates this to the current situation in northern Laos. The challenge is to now transfer this knowledge to the teak smallholders, professionals, educators and policy decision makers of Laos.